The Influence of the Mind Mapping Learning Model Regarding Concept Understanding Learning Outcomes - Didik Ishwahyudi; I Nyoman Sudana Degeng; Henry Praherdhiono; Dedi Kuswandi (JTP - Jurnal Teknologi Pendidikan, 2023)
The mind mapping learning model is a learning model that uses a combination of writing, images, symbols and colors at the same time so that it can maximize the function of the right and left brain to make it easier to remember and understand material concepts. This is the key to effective learning. The mind mapping learning model has often been used by previous researchers to test its effectiveness in increasing understanding of concepts in scientific knowledge (IPA). However, in this research, to test the power of the mind mapping learning model on the learning outcomes of understanding concepts in the social sciences group, namely in the Pancasila Education course in the Pancasila Ideology material which explains events and each event has an implied or abstract meaning so it needs to be concreted, the figures involved, the timeline or dynamics of events, with the characteristics of the material, Mind Mapping is needed to create the main ideas of the material to make it easier for students in the learning process. This research is experimental research which aims to test the effect of the mind mapping model on learning outcomes in understanding concepts.The results of the analysis of calculating the average final ability score of students (posttest) in the experimental group were 79.43. The results of the analysis of the calculation of the average final ability score of students (posttest) in the control group were 71.87. Based on the results of the questionnaire, data was obtained that students liked learning Pancasila Education with Pancasila Ideology material using the Mind Mapping model, because it has been proven to help students understand the concept of Pancasila Ideology material. Students are also motivated to learn Pancasila Education through the phases in the Mind Mapping model and the character of the model through interesting content.